Hungarian Monitoring, 25 May 1990 . [Magyar rádiófigyelő], 1990. május 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Anna Petrasovits' speech at the Socialist International meeting in Cairo - About Mitterrand's USSR visit - Railways strike in Poland - Kohl's speech at the disarmament conference - Soviets suspend troop withdrawals from the GDR Domestic Affairs: - József Antall visits Berlin - Ambassadors to resign - National trade unions roundtable - 5,000 Soviet apprentices arrive in Hungary to help the withdrawal process - The Bavarian State minister in talks in Hungary Economy: - The privatization process can be accelerated - Common market support to solve employment problems Külpolitika: - Kairóban ülésezik a Szocialista Internacionálé, Petrasovits felszólalt - Mitterrand szovjetunióbeli látogatásáról - Vasutassztrájk Lengyelországban - Kohl beszéde a leszerelési konferencián - Felfüggesztették a szovjet csapatok kivonását az NDK-ból Belpolitika: - Antall József Berlinbe utazik - Nagykövetek felmentése - Országos szakszervezeti kerekasztal - Ötezer újonc szovjet katona érkezik a csapatkivonulás segítésére - Magyarországon tárgyal a bajor államminiszter Gazdaság: - Fokozott ütemű privatizálás kezdődhet - A Közös Piac támogatása a foglalkoztatási gondok megoldására